2022
DOI: 10.1080/21655979.2022.2053032
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Forkhead box O1-aquaporin 5 axis mitigates neuropathic pain in a CCI rat model through inhibiting astrocytic and microglial activation

Abstract: Forkhead box O1 (FoxO1) is a critical molecule in modulating cell growth, differentiation and metabolism, acting as a vital transcription factor. This study explored the role of FoxO1 in chronic constriction injury (CCI)-induced neuropathic pain (NP). Microglial and astrocyte activation was achieved with lipopolysaccharide (LPS, 100 ng/mL) to establish an in-vitro NP model. Morphological alterations in LPS-induced microglia and astrocytes were assayed by light microscopy. The levels of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Similar to previous reports [ 32 , 33 ], we used LPS to establish the in vitro neuropathic pain condition, and compared the effect of LPS on astrocytes with the effect of H 2 O 2 , a widely used inducer of cell senescence [ 34 ]. In the astrocyte cultures, the proportion of cells that robustly expressed SA β-Gal was increased after treatment with either LPS ( P Veh versus LPS = 0.005) or H 2 O 2 ( P Veh versus H2O2 = 0.003), when compared with the control (Con) cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to previous reports [ 32 , 33 ], we used LPS to establish the in vitro neuropathic pain condition, and compared the effect of LPS on astrocytes with the effect of H 2 O 2 , a widely used inducer of cell senescence [ 34 ]. In the astrocyte cultures, the proportion of cells that robustly expressed SA β-Gal was increased after treatment with either LPS ( P Veh versus LPS = 0.005) or H 2 O 2 ( P Veh versus H2O2 = 0.003), when compared with the control (Con) cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Aquaporins, mainly responsible for water transport and clearance, play an important role in the development of CNS diseases. Studies have shown that AQP1, AQP2, AQP4, AQP5, and AQP9 are directly or indirectly related to neuropathic pain, and among them, AQP4 is closely related to neuropathic pain [13][14][15][16][17]. The CNS is sensitive to changes in the surrounding environment and lacks traditional lymphatic pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of rats and mice, the expression of AQP5 was up-regulated after crushed sciatic nerve injury, and neuropathic pain is one of the main symptoms of sciatic nerve injury, suggesting that AQP5 may be related to neuropathic pain [40]. In addition, topical administration of gabapentin was found to alleviate neuropathic ocular pain by inducing AQP5 expression in the lacrimal gland, and resveratrol was found to mitigate neuropathic pain by inhibiting AQP5 activation caused by chronic contractile injury [16,135]. Moreover, studies have indicated that AQP5 colocalizes with AQP2 in the kidney, and AQP5 can also regulate AQP2 expression, which is associated with neuropathic pain [15,41,136].…”
Section: Aqp5mentioning
confidence: 99%
See 1 more Smart Citation
“… 19 Furthermore, the FoxO1–AQP5 axis alleviates chronic constriction injury (CCI)-induced neuropathic pain (NP) by modulating the ERK and p38 MAPK signaling pathways. 20 However, the effect and mechanism of AQP5 on the LG nerve remain unclear.…”
mentioning
confidence: 99%